La teocrazia Crisi e trasformazione di un modello politico nell'Europa del XVIII secolo - Richichi, Iolanda (Premio Tesi di Dottorato, 2016)
This study analyses the crisis and transformations of theocracy as a political model in Europe in the first half of the 18th century. The work focuses on the transition from a positive and normative seventeenth-century consideration of theocracy, associated with the Jewish people, to its description in the 18th century as a universal, negative and primitive model. To this end, three authors are examined in their role of emblematic figures of this change, namely: Jacques Basnage, John Toland and Giambattista Vico. The study then highlights a radicalisation phase in mid-eighteenth-century France in the works by Nicolas Antoine Boulanger, and ends with the description of Boulanger's theocracy in Diderot and d'Alembert's Encyclopédie.